Pre-modern glocalization and ancient texts in the online 21st century: explorations in and between translations, communications, and inter-civilizational encounters - Inglis, David (Frontiers in Communication, 2024)
Examining some very old things using social-theoretical thinking can shed new light on some very recent ones. This paper argues that the movement into and through digital environs of ancient texts of religious, spiritual, and other forms of significance in recent years is just the latest iteration of very long-term glocalizing processes. These involve specific types of intricate and crisscrossing intra-and inter-civilizational modes of communication and mediation, namely translation practices. The paper sets out an account of inter-civilizational encounters in history, focusing on how texts often taken by many people today as direct expressions of the divine are in fact the results of the activities of those glocalizing actors known as translators. Studies of 21 st century digital glocalization, virtual religion, and related areas will benefit from further considering textual translation practices, as these are embedded within the long-term history of contacts between civilizational constellations. The historical unfoldings of ancient texts, when these have been subjected to glocalizing inter-civilizational processes, are more akin to online forms of communication than one might think. Thinking through such matters generates more capacious accounts of historical and contemporary glocalization and the glocality of civilizations.